Model'nye charakteristiki soderžanija sorevnovatel'nych upražnenij kvalificirovannych gimnastov v sportivnoj aerobike - Pozdeeva, E. A.; Pshenichnikova, G. N.; Korichko, Y. V. (Theory and Practice of Physical Culture, 2018)
The study analyzes basics of the technical and artistic performance rating model for correction of sport aerobics routines in the context of modern rules of individual competitions. The study included expert analyses of the video replays of the competitive routines in the World, Russian and Siberian Federal Regional championships. The analyses resulted in summaries of the routine contents and routine quality ratings and provided a basis for a technical and artistic performance rating model for the modern sport aerobics. The educational experiment and analyses were completed at CYSS #1 and CYORSS #18 in Omsk city in 2002-2018 with 60 elite athletes sampled for the model testing experiment. The model was designed to rate the technical and artistic/ aesthetic aspects of the competitive routines and rank them by three (low, moderate and high) levels. The study data and analyses helped clarify the model characteristics of the competitive routines in elite sport aerobics versus the execution rank/ difficulty level with the guiding scores for artistic merits.